Repertorio Americano: intelectuales y medio ambiente (1930-1952) - Urbina Gaitán, Chester (2018)
The aim of this article is to classify and to place in a context different texts, like poems and essays, about environmental preservation, published in Repertorio Americano during 1930-1952, related to environmental education and nature.